PRACTICE ASSESSMENT OF ENGLISH TEACHERS IN STATE MADRASAH SCHOOL IN MATARAM CITY - Pauzan, Pauzan; Ribahan, Ribahan (English Review: Journal of English Education, 2022)
This study aims to describe the assessment practices carried out by English teachers of state madrasah schools in Mataram City at the stages of planning, implementation, supervision, and recording. In this descriptive study, the researcher used qualitative and quantitative descriptive approaches. A total of 18 teachers from both state MTS and MA in the city of Mataram participated in the study. The data collection technique used a questionnaire in the form of a google form containing a number of statements related to the assessment practice at the four stages of the assessment with the answer format using a Likert scale with a range of answers strongly disagree, disagree, not sure, agree, and strongly agree. The data were the results of the average calculation of each item was analyzed descriptively. The results of the study showed that (1) teachers were not sure to ask for parental approval before the assessment was carried out, (2) teachers agreed that the assessment was carried out within a certain time, according to the situation and conditions and accompanied by feedback, (3) teachers felt hesitant to share the findings of the assessment with fellow teachers and the involvement of parents in the assessment process, and (4) the teacher felt aware and responsible for recording or documenting the results of the assessment that were carried out. Thus, assessment is an important part that cannot be separated from learning activities and teachers are expected to keep conducting assessments.